Optical Devices
Patent Information
- Application Number
- JP2024544367
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-11
- Filing Date
- 2023-02-10
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-02-10
AI Technical Summary
【0134】 本出願は光学デバイスに関する。本出願の光学デバイスは液晶セルのセルギャップが適切に維持され、上部基板と下部基板の優秀な付着力を有し、高温および高圧のオートクレーブ工程後に押され黒点を防止することができる。
Smart Images

Figure 2025504647000001_ABST
Abstract
Description
[Technical field]
[0001] The present application relates to optical devices.
[0002] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0018465 dated February 11, 2022, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference. [Background technology]
[0003] For the long-term stability and large-area scalability of a liquid crystal film cell using a flexible substrate, it is important to maintain a cell gap between the upper and lower substrates and to provide adhesive strength between the upper and lower substrates.
[0004] Non-Patent Document 1 ("Tight Bonding of Two Plastic Substrates for Flexible LCDs" SID Symposium Digest, 38, pp.653-656 (2007)) discloses a technique of forming a pillar or wall-shaped organic film pattern of the cell gap height on one substrate and fixing it to the opposite substrate using an adhesive. However, this technique requires that the adhesive be located only on the pillar or wall surfaces, and the technique of micro-stamping the adhesive on the pillar or wall surfaces is highly difficult to process, difficult to control the thickness and area of the adhesive, and high possibility of the adhesive squeezing out when the upper and lower substrates are bonded, which may contaminate the alignment film or liquid crystal. Summary of the Invention [Problem to be solved by the invention]
[0005] In order to maintain the cell gap of the liquid crystal cell and ensure the adhesion between the upper and lower substrates, it is possible to consider forming a spacer and an alignment film on the lower substrate, and forming an adhesive layer having liquid crystal alignment and adhesion on the upper substrate before bonding. However, when the liquid crystal cell is subjected to an autoclave process in which the liquid crystal cell is bonded at high temperature and high pressure, there is a problem that black spots are generated due to pressing. The object of the present application is to provide an optical device in which the cell gap of the liquid crystal cell is appropriately maintained, the upper and lower substrates have excellent adhesion, and the pressed black spots are not generated even after the autoclave process at high temperature and high pressure. [Means for solving the problem]
[0006] The present application relates to an optical device. The optical device may include a liquid crystal cell. FIG. 1 exemplarily illustrates the structure of the liquid crystal cell. The liquid crystal cell may include an upper substrate, a lower substrate, and a liquid crystal layer containing a liquid crystal compound between the upper substrate and the lower substrate. The upper substrate may include a first base layer 10a and a first adhesive layer 10c. The upper substrate may further include a first electrode layer 10b between the first base layer 10a and the adhesive layer 10c. The lower substrate may include a second base layer 20a and a spacer 20c. The lower substrate may further include a second electrode layer 20b between the second base layer 20a and the spacer 20c. Also, the lower substrate may further include an alignment film 20d on the spacer 20c. A liquid crystal layer 30 filled with a liquid crystal compound may exist in the space between the upper substrate and the lower substrate.
[0007] As the first and second substrate layers, for example, inorganic films such as glass films, crystalline or non-crystalline silicone films, quartz or ITO (Indium Tin Oxide) films, and polymer films can be used.
[0008] In one example, the first substrate layer and the second substrate layer may each be a polymer film in terms of realizing a flexible element. Examples of the polymer film include, but are not limited to, triacetyl cellulose (TAC); cycloolefin copolymer (COP) such as norbornene derivatives; poly(methyl methacrylate) (PMMA); polycarbonate (PC); polyethylene (PE); polypropylene (PP); polyvinyl alcohol (PVA); diacetyl cellulose (DAC); polyacrylate (PAC); polyether sulfone (PES); polyetheretherketon (PEEK); polyphenylsulfone (PPS), polyetherimide (PEI); polyethylenemaphthatlate (PEN); polyethyleneterephtalate (PET); polyimide (PI); polysulfone (PSF); polyarylate (PAR) or amorphous fluororesin. The first substrate layer and the second substrate layer may have a coating layer of gold, silver, silicon dioxide, silicon monoxide, or other silicon compound, or an anti-reflection layer, if necessary.
[0009] In one example, an optically anisotropic film may be used as the first and second substrate layers. Such an optically anisotropic film generally has anisotropic mechanical properties, and by utilizing such anisotropy, a liquid crystal cell or optical device having excellent durability can be provided.
[0010] In one example, the first substrate layer and the second substrate layer may each be a polymer film having an in-plane retardation value of 4,000 nm or more at a wavelength of 550 nm. The in-plane retardation value may be specifically 5,000 nm or more, 6,000 nm or more, 7,000 nm or more, 8,000 nm or more, or 9,000 nm or more, and may be 50,000 nm or less, 40,000 nm or less, 30,000 nm or less, 20,000 nm or less, 18,000 nm or less, 16,000 nm or less, 15,000 nm or less, or 12,000 nm or less. This may be advantageous in providing a liquid crystal cell without optical defects such as rainbow phenomenon.
[0011] In this specification, the in-plane retardation is a physical quantity defined by the following mathematical formula A. [Formula A] Rin = d × (nx-ny) In Formula A, Rin is an in-plane retardation, nx is a refractive index in the slow axis direction of the film, ny is a refractive index in the fast axis direction of the film, and d is a thickness of the film. nx and ny are refractive indices of the x-axis and y-axis of the film, respectively. The x-axis is a direction parallel to the in-plane slow axis of the film, and the y-axis is a direction parallel to the in-plane fast axis of the film, and the x-axis and y-axis may be perpendicular to each other in the plane.
[0012] The specific type of the film that can be used as the base layer is not particularly limited as long as it shows the in-plane retardation in the range mentioned above. For example, an anisotropic polymer film that is given optical anisotropy by stretching can be used. Examples of the polymer film include polyolefin films such as polyethylene films or polypropylene films, cycloolefin polymer (COP) films such as polynorbornene films, cellulose ester polymer films such as polyvinyl chloride films, polyacrylonitrile films, polysulfone, polyacrylate films, PVA (poly(vinyl alcohol)) films or TAC (Triacetyl cellulose) films, polyester films or polycarbonate films, and copolymer films of two or more monomers among the monomers that form the polymers.
[0013] As one example, the film may be a polyester film such as a PET (poly(ethylene terephthalate)) film. Films exhibiting an in-plane retardation in the above-mentioned range are well known in the industry, and in the case of polymer films, such films not only exhibit large optical anisotropy but also exhibit asymmetric mechanical properties due to stretching during the manufacturing process. A representative example of such retardation films known in the industry is a stretched polyester film such as a stretched PET (poly(ethylene terephthalate)) film.
[0014] When the anisotropic film is applied simultaneously to the first and second substrate layers, the substrates may be arranged such that the slow axes therebetween are parallel or perpendicular to each other.
[0015] As an example, the film may be a polyester film such as a PET film, but the type of film that may be used as the substrate in the present application is not limited thereto.
[0016] In one example, the first and second substrate layers may each have a thickness of about 10 μm to about 1,000 μm. As another example, the substrate layers may each have a thickness of 20 μm or more, 40 μm or more, 60 μm or more, 80 μm or more, 100 μm or more, 120 μm or more, or 140 μm or more, and may each have a thickness of 900 μm or less, 800 μm or less, 700 μm or less, 600 μm or less, 500 μm or less, or about 400 μm or less. When the thicknesses of the first and second substrate layers are within the above ranges, it may be advantageous to reduce appearance defects such as wrinkles when the liquid crystal cell is bonded to an outer substrate to manufacture an optical device.
[0017] The adhesive layer may be present on the inner surface of the first substrate layer. In this specification, the "inner surface" of the components included in the liquid crystal cell may refer to the surface facing the liquid crystal layer. By using such an adhesive layer, adhesion between the upper and lower substrates can be provided so that separation of the liquid crystal cell does not occur during or after the bonding process for supporting the liquid crystal composition between the upper and lower substrates. In addition, the adhesive layer may be advantageous in roll-to-roll processability and in preventing the flow of the liquid crystal composition.
[0018] In the present specification, the adhesive layer may be, for example, a layer of an adhesive composition. In the present specification, the term "adhesive composition layer" may mean a layer formed by coating or curing an adhesive composition. The term "curing of an adhesive composition" may mean realizing a crosslinked structure in the adhesive composition through a physical or chemical action or reaction of components contained in the adhesive composition. Curing may be induced, for example, by maintaining at room temperature, applying moisture, applying heat, irradiating with active energy rays, or by proceeding with two or more of the above processes together, and the type of adhesive composition in which curing is induced depending on each case may be called, for example, a room temperature curing adhesive composition, a moisture curing adhesive composition, a heat curing adhesive composition, an active energy ray curing adhesive composition, or a hybrid curing adhesive composition.
[0019] The pressure-sensitive adhesive layer may be optically transparent. The pressure-sensitive adhesive layer may have an average transmittance of about 80% or more, 85% or more, 90% or more, or 95% or more in the visible light region, for example, wavelengths of 380 nm to 780 nm.
[0020] The adhesive layer may be a liquid crystal aligning adhesive layer. The adhesive layer may be, for example, a vertically aligning adhesive layer or a horizontally aligning adhesive layer. In this specification, the term "vertically aligning adhesive" may mean an adhesive that imparts a vertical alignment force to adjacent liquid crystal compounds and has an adhesive force capable of bonding an upper substrate and a lower substrate. In this specification, the term "horizontally aligning adhesive" may mean an adhesive that imparts a horizontal alignment force to adjacent liquid crystal compounds and has an adhesive force capable of bonding an upper substrate and a lower substrate. The pretilt angle of the adjacent liquid crystal compounds relative to the vertically aligning adhesive may be within a range of 80 degrees to 90 degrees, 85 degrees to 90 degrees, or about 87 degrees to 90 degrees, and the pretilt angle of the adjacent liquid crystal compounds relative to the horizontally aligning adhesive may be within a range of 0 degrees to 10 degrees, 0 degrees to 5 degrees, or 0 degrees to 3 degrees. According to one embodiment of the present application, the adhesive layer may be a vertically aligning adhesive layer.
[0021] In this specification, the pretilt angle may refer to the angle that the director of the liquid crystal compound makes with respect to the liquid crystal alignment adhesive or alignment film and a plane horizontal thereto when no voltage is applied. In this specification, the director of the liquid crystal compound may refer to the optical axis or slow axis of the liquid crystal layer. Alternatively, the director of the liquid crystal compound may refer to the long axis direction when the liquid crystal compound is rod-shaped, or may refer to the axis parallel to the normal direction of the disc plane when the liquid crystal compound is discotic.
[0022] When the adhesive layer is a vertically oriented adhesive layer, the surface energy of the adhesive layer may be 16 mN / m or less. The lower limit of the surface energy may be, for example, 5 mN / m or more. When the adhesive layer is a horizontally oriented adhesive layer, the surface energy of the adhesive layer may be more than 16 mN / m. The upper limit of the surface energy may be, for example, 50 mN / m or less. The surface energy may be measured using a drop shape analyzer (DSA100 product of KRUSS). Specifically, the process of dropping deionized water, which has a known surface tension, onto the surface of the adhesive and measuring the contact angle is repeated five times, and the average value of the five contact angles obtained is calculated. In the same manner, the process of dropping diiodomethane, which has a known surface tension, onto the surface of the adhesive and measuring the contact angle is repeated five times, and the average value of the five contact angles obtained is calculated. Then, the surface energy can be calculated by substituting the value (Strom value) related to the surface tension of the solvent using the Owens-Wendt-Rabel-Kaelble method using the average contact angles for deionized water and diiodomethane. The surface energy (γsurface) of the sample can be calculated by taking into account the dispersion force between non-polar molecules and the interaction force between polar molecules (γsurface = γdispersion + γpolar), and the ratio of the polar term (γpolar) in the surface energy γsurface can be defined as the polarity of the surface.
[0023] The thickness of the adhesive layer may be, for example, within a range of 3 μm to 15 μm. When the thickness of the adhesive layer is within this range, it may be advantageous to minimize defects such as pressure or gathering of the adhesive when used in manufacturing a liquid crystal cell while ensuring adhesion between the upper and lower substrates.
[0024] The adhesive layer may be made of various types of adhesives known in the industry as OCA (Optically Clear Adhesive). The adhesive may be different from OCR (Optically Clear Resin) type adhesives, which are cured after the objects are bonded, in that the adhesive is cured before the objects are bonded.
[0025] The adhesive layer may include a silicone adhesive. In the case of a silicone adhesive, the adhesive composition may include a curable silicone compound as an adhesive resin. An adhesive composition including a curable silicone compound as an adhesive resin may be called a silicone composition. The silicone adhesive may include a cured product of a curable silicone compound as an adhesive resin. When a silicone adhesive is used, it may be suitable for exerting a vertical alignment force on the liquid crystal due to the difference in surface energy with the liquid crystal, and may also be advantageous in terms of preventing contamination of the liquid crystal. The type of the curable silicone compound is not particularly limited, and for example, a heat-curable silicone compound or an ultraviolet-curable silicone compound may be used.
[0026] In one example, the curable silicone compound can be an addition curable silicone compound.
[0027] Specifically, examples of the addition-curable silicone compound include, but are not limited to, (1) organopolysiloxanes containing two or more alkenyl groups in the molecule and (2) organopolysiloxanes containing two or more silicon-bonded hydrogen atoms in the molecule.
[0028] The silicone compounds as described above can form a cured product by an addition reaction in the presence of a catalyst such as platinum.
[0029] The (1) organopolysiloxane is a main component constituting a silicone cured product and contains at least two alkenyl groups per molecule. Specific examples of the alkenyl group include vinyl, allyl, butenyl, pentenyl, hexenyl, and heptenyl groups, among which vinyl groups are usually used, but are not limited thereto. In the (1) organopolysiloxane, the bonding position of the alkenyl group is not particularly limited. For example, the alkenyl group may be bonded to the end of a branched chain and / or to a side chain of a branched chain. In the (1) organopolysiloxane, examples of the substituents that may be contained in addition to the alkenyl include alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, and heptyl; aryl groups such as phenyl, tolyl, xylyl, and naphthyl; aralkyl groups such as benzyl and phenethyl; and halogen-substituted alkyl groups such as chloromethyl, 3-chloropropyl, and 3,3,3-trifluoropropyl. Of these, methyl and phenyl groups are usually used, but the present invention is not limited to these.
[0030] The molecular structure of the organopolysiloxane (1) is not particularly limited, and may have any shape, such as linear, branched, cyclic, network, or linear with some branching, etc. Among the molecular structures described above, those having a linear molecular structure are usually used, but are not limited thereto.
[0031] More specific examples of the organopolysiloxane (1) include a dimethylsiloxane-methylvinylsiloxane copolymer having both branched chain ends blocked with trimethylsiloxane groups, a methylvinylpolysiloxane having both branched chain ends blocked with trimethylsiloxane groups, a dimethylsiloxane-methylvinylsiloxane-methylphenylsiloxane copolymer having both branched chain ends blocked with trimethylsiloxane groups, a dimethylpolysiloxane having both branched chain ends blocked with dimethylvinylsiloxane groups, a methylvinylpolysiloxane having both branched chain ends blocked with dimethylvinylsiloxane groups, a dimethylsiloxane-methylvinylsiloxane copolymer having both branched chain ends blocked with dimethylvinylsiloxane groups, a dimethylsiloxane-methylvinylsiloxane-methylphenylsiloxane copolymer having both branched chain ends blocked with dimethylvinylsiloxane groups, 1 2 SiO 2 / 2 Siloxane units represented by and R 1 2 R 2 SiO 1 / 2 The siloxane unit represented by and SiO 4 / 2 Organopolysiloxane copolymers containing siloxane units represented by R 1 2 R 2 SiO 1 / 2 The siloxane unit represented by and SiO 4 / 2 Organopolysiloxane copolymers containing siloxane units represented by R 1 R 2 SiO 2 / 2 Siloxane units represented by and R 1 SiO 3 / 2 Siloxane units denoted by R 2 SiO 3 / 2 and mixtures of two or more of the above. 1is a hydrocarbon group other than an alkenyl group, specifically, an alkyl group such as a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, or a heptyl group; an aryl group such as a phenyl group, a tolyl group, a xylyl group, or a naphthyl group; an aralkyl group such as a benzyl group or a phenethyl group; a halogen-substituted alkyl group such as a chloromethyl group, a 3-chloropropyl group, or a 3,3,3-trifluoropropyl group; 2 is an alkenyl group, specifically, a vinyl group, an allyl group, a butenyl group, a pentenyl group, a hexenyl group, a heptenyl group, or the like.
[0032] In the addition curable silicone composition, the (2) organopolysiloxane can crosslink the (1) organopolysiloxane. In the (2) organopolysiloxane, the bond position of the hydrogen atom is not particularly limited, and may be bonded to, for example, the end of a branched chain and / or a side chain. In the (2) organopolysiloxane, the type of substituent that may be contained in addition to the silicon-bonded hydrogen atom is not particularly limited, and examples thereof include alkyl groups, aryl groups, aralkyl groups, and halogen-substituted alkyl groups, as mentioned in the (1) organopolysiloxane, and among these, methyl groups or phenyl groups are usually used, but are not limited thereto.
[0033] The molecular structure of the (2) organopolysiloxane is not particularly limited, and may have any shape, such as linear, branched, cyclic, network, or partially branched linear, etc. Among the above molecular structures, those having a linear molecular structure are usually used, but are not limited thereto.
[0034] More specific examples of the organopolysiloxane (2) include methylhydrogenpolysiloxanes blocked at both branched chain terminals with trimethylsiloxane groups, dimethylsiloxane-methylhydrogen copolymers blocked at both branched chain terminals with trimethylsiloxane groups, dimethylsiloxane-methylhydrogensiloxane-methylphenylsiloxane copolymers blocked at both branched chain terminals with trimethylsiloxane groups, dimethylpolysiloxanes blocked at both branched chain terminals with dimethylhydrogensiloxane groups, dimethylsiloxane-methylphenylsiloxane copolymers blocked at both branched chain terminals with dimethylhydrogensiloxane groups, methylphenylpolysiloxanes blocked at both branched chain terminals with dimethylhydrogensiloxane groups, R 1 3 SiO 1 / 2 Siloxane units represented by and R 1 2 HSiO 1 / 2 The siloxane unit represented by and SiO 4 / 2 Organopolysiloxane copolymers containing siloxane units represented by R 1 2 HSiO 1 / 2 The siloxane unit represented by and SiO 4 / 2 Organopolysiloxane copolymers containing siloxane units represented by R 1 HSiO 2 / 2 Siloxane units represented by and R 1 SiO 3 / 2 Siloxane units represented by HSiO 3 / 2 and mixtures of two or more of the above. 1 is a hydrocarbon group other than an alkenyl group, and specifically may be an alkyl group such as a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, or a heptyl group; an aryl group such as a phenyl group, a tolyl group, a xylyl group, or a naphthyl group; an aralkyl group such as a benzyl group or a phenethyl group; or a halogen-substituted alkyl group such as a chloromethyl group, a 3-chloropropyl group, or a 3,3,3-trifluoropropyl group.
[0035] The content of the (2) organopolysiloxane is not particularly limited as long as it is contained to an extent that allows suitable curing. For example, the (2) organopolysiloxane may be contained in an amount such that the number of silicon-bonded hydrogen atoms is 0.5 to 10 per alkenyl group contained in the (1) organopolysiloxane. Within this range, curing can be sufficiently advanced and heat resistance can be ensured.
[0036] The addition-curable silicone composition may further contain appropriate additives in appropriate proportions required from the standpoint of improving storage stability, handling, and workability.
[0037] In another embodiment, the silicone composition is a condensation curable silicone composition, and may include, for example, (a) an alkoxy group-containing siloxane polymer; and (b) a hydroxyl group-containing siloxane polymer.
[0038] The (a) siloxane polymer may be, for example, a compound represented by the following chemical formula I: [Chemical formula I] R 1 a R 2 b SiO c (OR 3 ) d In formula I, R 1 and R 2 each independently represents a hydrogen atom or a substituted or unsubstituted monovalent hydrocarbon group; R 3 represents an alkyl group, and R 1 , R 2 and R 3 When multiple of each are present, they may be the same or different, a and b each independently represent a number greater than 0 and less than 1, a+b represents a number greater than 0 and less than 2, c represents a number greater than 0 and less than 2, d represents a number greater than 0 and less than 4, and a+b+c×2+d is 4.
[0039] In the definition of Chemical Formula I, the monovalent hydrocarbon may be, for example, an alkyl group having 1 to 8 carbon atoms, a phenyl group, a benzyl group, or a tolyl group, and in this case, the alkyl group having 1 to 8 carbon atoms may be, for example, a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, or an octyl group. In addition, in the definition of Chemical Formula 1, the monovalent hydrocarbon group may be substituted with a known substituent such as, for example, a halogen, an amino group, a mercapto group, an isocyanate group, a glycidyl group, a glycidoxy group, or a ureido group.
[0040] In the definition of Formula I, R 3 Examples of the alkyl group include a methyl group, an ethyl group, a propyl group, an isopropyl group, and a butyl group. Among the alkyl groups, a methyl group or an ethyl group is usually used, but is not limited thereto.
[0041] A branched or tertiary crosslinked siloxane polymer can be used among the polymers of chemical formula I. In addition, the (a) siloxane polymer may have residual hydroxyl groups within a range that does not impair the purpose, specifically, within a range that does not inhibit the dealcoholization reaction.
[0042] The (a) siloxane polymer can be produced, for example, by hydrolysis and condensation of a polyfunctional alkoxysilane or a polyfunctional chlorosilane. An average technician in this field can easily select a suitable polyfunctional alkoxysilane or chlorosilane for the desired (a) siloxane polymer, and can easily control the conditions of the hydrolysis and condensation reaction using the same. Meanwhile, when producing the (a) siloxane polymer, a suitable monofunctional alkoxysilane may be used in combination depending on the purpose.
[0043] As the (a) siloxane polymer, for example, commercially available organosiloxane polymers such as X40-9220 or X40-9225 from Shin-Etsu Silicones, and XR31-B1410, XR31-B0270 or XR31-B2733 from GE Toray Silicones can be used.
[0044] As the hydroxyl-containing siloxane polymer (b) contained in the condensation-curable silicone composition, for example, a compound represented by the following chemical formula II can be used. [Chemical formula II] [ka] In formula II, R 4 and R 5 each independently represents a hydrogen atom or a substituted or unsubstituted monovalent hydrocarbon group; R 4 and R 5 When a plurality of each of is present, they may be the same or different, and n represents an integer of 5 to 2,000.
[0045] In the definition of chemical formula II, specific examples of the monovalent hydrocarbon group include the same hydrocarbon groups as those in the case of chemical formula I above.
[0046] Said (b) siloxane polymer can be produced, for example, by hydrolysis and condensation of dialkoxysilane and / or dichlorosilane. An average technician in this field can easily select a dialkoxysilane or dichlorosilane suitable for the desired (b) siloxane polymer, and can easily control the conditions of hydrolysis and condensation reaction using it. As said (b) siloxane polymer, for example, commercially available bifunctional organosiloxane polymers such as XC96-723, YF-3800, YF-3804, etc., from GE Toray Silicone Co., Ltd. can be used.
[0047] According to the present application, by controlling the storage modulus and tan delta value at 110°C of the adhesive layer, it is possible to prevent black spots after autoclaving at high temperature and pressure. In this specification, tan delta (tan δ value) is G″ / G' (G′ is the storage modulus and G″ is the loss modulus). The storage modulus (G′) can mean the elasticity of the adhesive, and the loss modulus (G″) can mean the viscosity of the adhesive. The higher the storage modulus, the harder the adhesive is and the higher the elasticity, and the higher the loss modulus, the softer the adhesive is and the higher the viscosity. Since an adhesive has both elasticity and viscosity, it can be expressed by the loss factor tan δ value, which is the ratio of the loss modulus and the storage modulus. If the tan δ value is smaller than 1, it can be said that the elasticity is high, and if it is larger than 1, it can be said that the viscosity is high.
[0048] In one example, the storage modulus of the pressure-sensitive adhesive layer at a temperature of 110° C. and a frequency of 1 rad / sec may be 18,000 Pa or more. The storage modulus of the pressure-sensitive adhesive layer at a temperature of 110° C. and a frequency of 1 rad / sec may be 100,000 Pa or less. The storage modulus of the pressure-sensitive adhesive layer may be specifically 19,000 Pa or more, 19,500 Pa or more, 20,000 Pa or more, 20,500 Pa or more, 21,000 Pa or more, 21,500 Pa or more, 22,000 Pa or more, 22,500 Pa or more, 23,000 Pa or more, 23,500 Pa or more, 24,000 Pa or more, 24,500 Pa or more, 25,000 Pa or more, 30,000 Pa or more, 35,000 Pa or more, 40,000 Pa or more, 45,000 Pa or more, or 50,000 Pa or more, and more preferably 90,000 Pa or more. Pa or less, 85,000 Pa or less, 80,000 Pa or less, 75,000 Pa or less, 70,000 Pa or less, 65,500 Pa or less, 60,000 Pa or less, 55,000 Pa or less, 50,000 Pa or less, 45,500 Pa or less, 40,000 Pa or less, 35,500 Pa or less, 30,000 Pa or less, 25,000 Pa or less, 25,500 Pa or less, 24,000 Pa or less, 23,500 Pa or less, 23,000 Pa or less, 22,000 Pa or less, 21,000 Pa or less, or 20,000 Pa or less. When the storage modulus of the pressure-sensitive adhesive layer at a temperature of 110°C and a frequency of 1 rad / sec is within the above range, pressing and black spots can be prevented after high-temperature and high-pressure autoclaving.
[0049] In one example, the pressure-sensitive adhesive layer may have a storage modulus of 10,000 Pa or more at a temperature of 25° C. and a frequency of 1 rad / sec. The pressure-sensitive adhesive layer may have a storage modulus of 1,100,000 Pa or less at a temperature of 25° C. and a frequency of 1 rad / sec. The storage modulus of the pressure-sensitive adhesive layer is specifically 30,000 Pa or more, 35,000 Pa or more, 50,000 Pa or more, 100,000 Pa or more, 150,000 Pa or more, 200,000 Pa or more, 250,000 Pa or more, 300,000 Pa or more, 350,000 Pa or more, 400,000 Pa or more, 500,000 Pa or more, 600,000 Pa or more, 700,000 Pa or more, 800,000 Pa or more, 900,000 Pa or less. The storage modulus may be 900,000 Pa or less, 800,000 Pa or less, 700,000 Pa or less, 600,000 Pa or less, 500,000 Pa or less, 450,000 Pa or less, 400,000 Pa or less, 350,000 Pa or less, 300,000 Pa or less, 250,000 Pa or less, 200,000 Pa or less, 150,000 Pa or less, 100,000 Pa or less, or 50,000 Pa or less. When the storage modulus of the adhesive layer at a temperature of 25° C. and a frequency of 1 rad / sec is within the above range, it may be advantageous to ensure excellent electro-optical properties and appearance uniformity by minimizing defects such as pressure and gathering of the adhesive during the manufacture of a liquid crystal cell while ensuring adhesion between the upper and lower substrates.
[0050] In one example, the tangent delta value of the adhesive layer at a temperature of 110° C. and a frequency of 1 rad / sec may be 0.32 or less. The tangent delta value of the adhesive layer at a temperature of 110° C. and a frequency of 1 rad / sec may be 0.1 or more. The tangent delta value of the adhesive layer may be specifically 0.31 or less, 0.30 or less, 0.29 or less, 0.28 or less, 0.27 or less, 0.26 or less, 0.25 or less, 0.24 or less, 0.23 or less, or 0.22 or less, or 0.12 or more, 0.14 or more, 0.16 or more, 0.18 or more, 0.20 or more, 0.22 or more, 0.24 or more, 0.26 or more, 0.28 or more, or 0.30 or more. When the tangent delta value of the adhesive layer at a temperature of 110° C. and a frequency of 1 rad / sec is within the above range, pressing after high temperature and high pressure autoclaving can be prevented from black spots.
[0051] In one example, the pressure-sensitive adhesive layer may have a tangent delta value of 2.0 or less at a frequency of 1 rad / sec at a temperature of 25° C. The pressure-sensitive adhesive layer may have a tangent delta value of 0.1 or more at a frequency of 1 rad / sec at a temperature of 25° C. The tangent delta value of the pressure-sensitive adhesive layer may be specifically 0.1 or more, 0.2 or more, 0.3 or more, 0.4 or more, 0.5 or more, 0.6 or more, 0.7 or more, 0.8 or more, 0.9 or more, 1.0 or more, 1.1 or more, 1.2 or more, 1.3 or more, 1.4 or more, or 1.5 or more, and may be 2.0 or less, 1.9 or less, 1.8 or less, 1.7 or less, 1.6 or less, 1.5 or less, 1.4 or less, 1.3 or less, 1.2 or less, 1.1 or less, 1.0 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, or 0.45 or less. When the tangent delta value of the adhesive layer at a temperature of 25° C. and a frequency of 1 rad / sec is within the above range, it may be advantageous to ensure excellent electro-optical properties and appearance uniformity by minimizing defects such as pressure and gathering of the adhesive during the manufacture of the liquid crystal cell while ensuring adhesion between the upper and lower substrates.
[0052] Methods for controlling the storage modulus and tangent delta value of the adhesive layer are known, and the method for controlling the storage modulus and tangent delta value in the present application is not particularly limited. In one example, the storage modulus and tangent delta value of the adhesive layer can be controlled by appropriately adjusting the catalyst and crosslinker of the adhesive and / or adhesive composition and appropriately adjusting the curing conditions of the adhesive. The following are merely exemplary conditions for providing the adhesive of the present application, and the scope of the present application is not limited thereto.
[0053] In one embodiment, the adhesive and / or adhesive composition may further include a catalyst for curing. The catalyst may be, for example, a platinum-based catalyst. The content of the catalyst may be adjusted in consideration of the desired physical properties of the adhesive layer. The catalyst may be included in an amount of 0.1 parts by weight or more, 0.5 parts by weight or more, or 1 part by weight or more, and may be included in an amount of 1.5 parts by weight or less, 1.3 parts by weight or less, or 1.1 parts by weight or less, based on 100 parts by weight of the adhesive resin.
[0054] According to the examples of the present application, when all other conditions are the same except for the catalyst content, the higher the catalyst content, the lower the storage modulus and the lower the tangent delta value.
[0055] In one embodiment, the adhesive and / or adhesive composition may further include a crosslinker. The crosslinker may be, for example, a silane compound. The silane compound may be, for example, a compound represented by Chemical Formula 1 or Chemical Formula 2. The crosslinker may be included in an amount of 1 part by weight or more, 2 parts by weight or more, 3 parts by weight or more, 4 parts by weight or more, 5 parts by weight or more, 7 parts by weight or more, 10 parts by weight or more, 12 parts by weight or more, or 15 parts by weight or more, and may be included in an amount of 20 parts by weight or less, 19 parts by weight or less, 18 parts by weight or less, 17 parts by weight or less, 16 parts by weight or less, 15 parts by weight or less, 13 parts by weight or less, 11 parts by weight or less, 9 parts by weight or less, 7 parts by weight or less, 5 parts by weight or less, or 3 parts by weight or less, based on 100 parts by weight of the adhesive resin. [Chemical formula 1] [ka] R in Chemical Formula 1 1 ~R 8 may each independently be an alkyl group having 1 to 4 carbon atoms. 1 ~R 8 may each independently be an alkyl group having 1 to 3 carbon atoms or an alkyl group having 1 to 2 carbon atoms. 1 ~R 8 may each be a methyl group. [Chemical formula 2] [ka] In formula 2, R 1 is an alkyl group having 10 to 30 carbon atoms, and R 2 ~R 4 are each independently an alkyl group having 1 to 4 carbon atoms. In Chemical Formula 2, R 1 Specifically, R may be an alkyl group having 10 or more carbon atoms, 12 or more, 14 or more, 16 or more, or 18 or more carbon atoms. 1 Specifically, R may be an alkyl group having 30 or less, 28 or less, 26 or less, 24 or less, 22 or less, 20 or less, or 18 or less carbon atoms. The alkyl group may be a linear alkyl group. 2 ~R 4 may each independently be an alkyl group having 1 to 4 carbon atoms, an alkyl group having 1 to 3 carbon atoms, or an alkyl group having 1 to 2 carbon atoms. 2 ~R 4 may each be a methyl group.
[0056] In one example, the curing temperature for providing the adhesive layer may be, for example, within a range of about 140°C to 180°C. The curing time for providing the adhesive may be, for example, 3 minutes to 15 minutes. Specifically, the adhesive composition may be coated on a release film, and then cured under the above conditions to provide the adhesive layer. According to the examples of the present application, when the other conditions are the same except for the curing time, the longer the curing time, the higher the storage modulus and the lower the tangent delta value. According to the examples of the present application, when the other conditions are the same except for the curing temperature, the higher the curing temperature, the higher the storage modulus and the lower the tangent delta value.
[0057] The upper and lower substrates of the liquid crystal cell may be attached to each other by an adhesive layer. Specifically, the adhesive layer of the upper substrate may be attached to the spacer of the lower substrate. When an alignment film is formed on the spacer of the lower substrate, the area of the alignment film corresponding to the spacer may be attached to the adhesive layer of the upper substrate.
[0058] The liquid crystal compound can switch the alignment state by applying a voltage. As the liquid crystal compound, a liquid crystal compound whose alignment direction can be changed by applying an external action can be used. As used herein, the term "external action" can refer to any external factor that can affect the behavior of a substance contained in the liquid crystal layer, such as an external voltage. Therefore, a state without an external action can refer to a state without application of an external voltage or the like.
[0059] The type and properties of the liquid crystal compound may be appropriately selected in consideration of the purpose of the present application. In one example, the liquid crystal compound may be a nematic liquid crystal or a smectic liquid crystal. Nematic liquid crystal may refer to a liquid crystal in which rod-shaped liquid crystal molecules are arranged in parallel in the long axis direction of the liquid crystal molecules without any regularity in position, and smectic liquid crystal may refer to a liquid crystal in which rod-shaped liquid crystal molecules are regularly arranged to form a layered structure and are arranged in parallel with regularity in the long axis direction. According to one embodiment of the present application, the liquid crystal compound may be a nematic liquid crystal compound.
[0060] The nematic liquid crystal compound may be selected to have a clearing point of, for example, about 40° C. or more, 50° C. or more, 60° C. or more, 70° C. or more, 80° C. or more, 90° C. or more, 100° C. or more, or about 110° C. or more, or a phase transition point within the above range, i.e., a phase transition point from a nematic phase to an isotropic phase. In one example, the clearing point or phase transition point may be about 160° C. or less, 150° C. or less, or about 140° C. or less.
[0061] The liquid crystal compound may be a non-reactive liquid crystal compound. The non-reactive liquid crystal compound may mean a liquid crystal compound that does not have a polymerizable group. The polymerizable group may be exemplified by, but is not limited to, an acryloyl group, an acryloyloxy group, a methacryloyl group, a methacryloyloxy group, a carboxy group, a hydroxy group, a vinyl group, or an epoxy group, and may include known functional groups known as polymerizable groups.
[0062] The liquid crystal compound may have a positive or negative dielectric anisotropy. The absolute value of the dielectric anisotropy of the liquid crystal compound may be appropriately selected in consideration of the object of the present application. The term "dielectric anisotropy (Δε)" may mean the difference (ε / / -ε⊥) between the horizontal dielectric constant (ε / / ) and the vertical dielectric constant (ε⊥) of the liquid crystal. In this specification, the term horizontal dielectric constant (ε / / ) means a dielectric constant value measured along the direction of an electric field in a state where a voltage is applied so that the direction of the electric field caused by the director of the liquid crystal compound and the applied voltage is substantially horizontal, and the term vertical dielectric constant (ε⊥) means a dielectric constant value measured along the direction of the electric field in a state where a voltage is applied so that the direction of the electric field caused by the director of the liquid crystal compound and the applied voltage is substantially perpendicular. The dielectric anisotropy of the liquid crystal molecules may be in the range of 5 to 25.
[0063] The refractive index anisotropy (Δn) of the liquid crystal compound may be appropriately selected in consideration of the object of the present application. In this specification, the term "refractive index anisotropy" refers to the extraordinary refractive index (n e ) and ordinary refractive index (n o ) difference (n e -n oThe refractive index anisotropy of the liquid crystal compound may be, for example, 0.01 to 0.3. The refractive index anisotropy may be 0.01 or more, 0.05 or more, or 0.07 or more, and may be 0.3 or less, 0.2 or less, 0.15 or less, or 0.13 or less.
[0064] The liquid crystal layer may further include a dichroic dye. The dichroic dye may control the light transmittance variable property of the liquid crystal layer. In this specification, the term "dye" may mean a substance capable of intensively absorbing and / or transforming light within at least a part or the entire visible light range, for example, a wavelength range of 400 nm to 700 nm, and the term "dichroic dye" may mean a substance capable of anisotropic absorption of light within at least a part or the entire visible light range.
[0065] The liquid crystal layer containing the liquid crystal compound and the dichroic dye may be a GHLC layer (Guest Host Liquid Crystal Layer). In this specification, the term "GHLC layer (Guest Host Liquid Crystal Layer)" may refer to a functional layer in which the dichroic dye is arranged together with the liquid crystal compound, and which exhibits anisotropic light absorption characteristics in the alignment direction of the dichroic dye and in the direction perpendicular to the alignment direction. For example, the dichroic dye is a material whose light absorption rate changes depending on the polarization direction, and if it has a high absorption rate for light polarized in the long axis direction, it may be called a p-type dye, and if it has a high absorption rate for light polarized in the short axis direction, it may be called an n-type dye. In one example, when a p-type dye is used, polarized light vibrating in the long axis direction of the dye is absorbed, and polarized light vibrating in the short axis direction of the dye is less absorbed and can be transmitted. Hereinafter, unless otherwise specified, it is assumed that the dichroic dye is a p-type dye.
[0066] As the dichroic dye, for example, a known dye that is known to have a property of being aligned according to the alignment state of the liquid crystal compound by the so-called guest-host effect can be selected and used. Examples of such dichroic dyes include azo dyes, anthraquinone dyes, methine dyes, azomethine dyes, merocyanine dyes, naphthoquinone dyes, tetrazine dyes, phenylene dyes, quaterrylene dyes, benzothiadiazole dyes, diketopyrrolopyrrole dyes, squaraine dyes, and pyrromethene dyes, but the dyes applicable in the present application are not limited to the above.
[0067] The dichroic dye may have a dichroic ratio, i.e., the ratio of the absorption of light polarized parallel to the long axis of the dichroic dye divided by the absorption of light polarized parallel to the direction perpendicular to the long axis, of 5 or more, 6 or more, or 7 or more. The dye may satisfy the dichroic ratio at least at some wavelengths or at any one wavelength within the wavelength range of the visible light region, for example, about 380 nm to 700 nm or about 400 nm to 700 nm. The upper limit of the dichroic ratio may be, for example, about 20 or less, 18 or less, 16 or less, or 14 or less.
[0068] The content of the dichroic dye in the liquid crystal layer may be appropriately selected in consideration of the purpose of the present application. For example, the content of the dichroic dye in the liquid crystal layer may be 0.2 wt% or more. Specifically, the content of the dichroic dye may be 0.5 wt% or more, 1 wt% or more, 2 wt% or more, or 3 wt% or more. The upper limit of the content of the dichroic dye may be, for example, 10 wt% or less, 9 wt% or less, 8 wt% or less, 6 wt% or less, or 5 wt% or less. If the content of the dichroic dye in the liquid crystal layer is too low, it may be difficult to achieve the desired transmittance variable property, and if the content of the dichroic dye in the liquid crystal layer is too high, precipitation may occur. Therefore, it may be advantageous for the content of the dichroic dye to be within the above range.
[0069] The thickness of the liquid crystal layer is not particularly limited, and for example, the thickness of the liquid crystal layer may be about 0.01 μm or more, 0.05 μm or more, 0.1 μm or more, 0.5 μm or more, 1 μm or more, 1.5 μm or more, 2 μm or more, 2.5 μm or more, 3 μm or more, 3.5 μm or more, 4 μm or more, 4.5 μm or more, 5 μm or more, 5.5 μm or more, 6 μm or more, 6.5 μm or more, 7 μm or more, 7.5 μm or more, 8 μm or more, 8.5 μm or more, 9 μm or more, or 9.5 μm or more. The upper limit of the thickness of the liquid crystal layer is not particularly limited, and generally may be about 30 μm or less, 25 μm or less, 20 μm or less, or 15 μm or less.
[0070] The liquid crystal cell can switch the alignment state of the liquid crystal layer according to the applied voltage. In one example, when no voltage is applied to the liquid crystal cell, the liquid crystal layer can have a first alignment state, and when a voltage is applied to the liquid crystal cell, the liquid crystal layer can have a second alignment state different from the first alignment state. Examples of the first alignment state and / or the second alignment state include a horizontal alignment state, a vertical alignment state, a twist alignment state, a tilt alignment state, and a hybrid alignment state.
[0071] In this specification, a "horizontal alignment state" refers to a state in which the directors of the liquid crystal compound in the liquid crystal layer are aligned approximately parallel to the plane of the liquid crystal layer, and for example, the angle that the directors make with respect to the plane of the liquid crystal layer can be, for example, within a range of approximately -10 degrees to 10 degrees or -5 degrees to 5 degrees, or can be approximately 0 degrees.
[0072] As used herein, a "vertical alignment state" refers to a state in which the directors of the liquid crystal compound in the liquid crystal layer are aligned approximately perpendicular to the plane of the liquid crystal layer, and for example, the angle that the directors make with respect to the plane of the liquid crystal layer may be, for example, within a range of approximately 80 degrees to 100 degrees or 85 degrees to 95 degrees, or may be approximately 90 degrees.
[0073] In the present specification, the term "twisted alignment state" refers to a helical structure in which the directors of liquid crystal compounds are twisted along a virtual helical axis in a liquid crystal layer to form a layer. The twisted alignment state can be realized as a vertical, horizontal, or tilted alignment state, that is, the vertical twist alignment mode is a state in which individual liquid crystal compounds are twisted along a helical axis in a vertically aligned state to form a layer, the horizontal twist alignment mode is a state in which individual liquid crystal compounds are twisted along a helical axis in a horizontally aligned state to form a layer, and the tilted twist alignment mode is a state in which individual liquid crystal compounds are twisted along a helical axis in a tilted aligned state to form a layer.
[0074] In this specification, the term "hybrid alignment state" may refer to an alignment state in which the tilt angle, which is the angle that the director of a liquid crystal compound in a liquid crystal layer makes with respect to the plane of the liquid crystal layer, gradually increases or decreases along the thickness direction of the liquid crystal layer.
[0075] In one example, the first alignment state may be a twisted alignment state, i.e., the liquid crystal layer may be capable of switching between the twisted alignment and another alignment state through application of external energy.
[0076] In one embodiment, the liquid crystal layer can be switched between a twisted alignment state and a vertical alignment state. In one embodiment, the liquid crystal layer can be in a vertical alignment state when no voltage is applied, and in a twisted alignment state when a voltage is applied. The twisted alignment can be a horizontal twisted alignment.
[0077] The liquid crystal layer may further include a chiral dopant. When the liquid crystal layer includes a chiral agent, a twisted alignment state may be realized. The chiral agent (or chiral dopant) that may be included in the liquid crystal layer may be any agent capable of inducing a desired twisting without damaging the liquid crystal property, for example, nematic regularity. The chiral agent for inducing rotation in the liquid crystal compound must at least include chirality in its molecular structure. Examples of the chiral agent include a compound having one or more asymmetric carbons, a compound having an asymmetric point on a heteroatom such as a chiral amine or chiral sulfoxide, or a compound having an axially asymmetric, optically active site such as cumulene or binaphthol. The chiral agent may be, for example, a low molecular weight compound having a molecular weight of 1,500 or less. As the chiral agent, commercially available chiral nematic liquid crystals, such as chiral dopant liquid crystal S-811 available from Merck or LC756 available from BASF, may be used.
[0078] The application ratio of the chiral dopant can be selected so as to achieve a desired pitch (P). In general, the content (wt%) of the chiral dopant can be calculated by the formula 100 / (HTPХ), where HTP indicates the helical twisting power of the chiral dopant and is expressed in μm. -1The P is the pitch of the liquid crystal in the twisted alignment state, and may be expressed in μm. The pitch p of the liquid crystal layer may be measured by a measurement method using a wedge cell, specifically, by the method described in Simple method for accurate measurements of the cholesteric pitch using a "stripe-wedge Grandjean-Cano cell" by D. Podolskyy et al. (Liquid Crystals, Vol. 35, No. 7, July 2008, pp. 789-791). The HTP value may be measured by the measurement method using the wedge cell described above. Alternatively, the HTP value may be provided by a supplier of the liquid crystal and the chiral dopant. The content of the chiral dopant may be determined by taking into account the desired pitch with reference to the above method.
[0079] In one example, the pitch (unit: μm) of the liquid crystal in the twisted alignment state may be in the range of 15 μm to 50 μm, and more specifically, the pitch may be 16 μm or more, 17 μm or more, 18 μm or more, 19 μm or more, or 20 μm or more, and may be 50 μm or less, 45 μm or less, 40 μm or less, 35 μm or less, or 30 μm or less.
[0080] The upper substrate of the liquid crystal cell may further include a first electrode layer 10b between the first base layer 10a and the adhesive layer 10c. The first electrode layer 10b may be in contact with the inner surface of the first base layer 10a. The adhesive layer 10c may be in contact with the inner surface of the first electrode layer 10b. The lower substrate of the liquid crystal cell may further include a second electrode layer 20b between the second base layer 20a and the spacer 20c. The second electrode layer 20b may be in contact with the inner surface of the second base layer 20a. The spacer 20c may be in contact with the inner surface of the second electrode layer 20b.
[0081] The first electrode layer and the second electrode layer may perform a role of applying an external action, for example, application of an electric field, so that a material contained in the liquid crystal layer transmits or blocks incident light. In one example, the first electrode layer and / or the second electrode layer may include, but is not limited to, a conductive polymer, a conductive metal, a conductive nanowire, or a metal oxide such as ITO (Indium Tin Oxide). The upper first electrode layer and / or the second electrode layer may be formed by depositing, for example, the conductive polymer, the conductive metal, the conductive nanowire, or a metal oxide such as ITO (Indium Tin Oxide).
[0082] The lower substrate of the liquid crystal cell may further include an alignment film 20d. The alignment film 20d may be present on the spacer 20c. That is, the upper surface and / or the side surface of the spacer 20c may be in contact with the alignment film. The lower surface of the spacer 20c may be in contact with the second electrode layer 20b. Since the adhesive layer included in the upper substrate may have liquid crystal alignment properties, the upper substrate may not include an alignment film. That is, the inner surfaces of the first electrode layer 10b and / or the adhesive layer 10c may not include an alignment film.
[0083] In this specification, the combination of the first base layer, the first electrode layer, and the adhesive layer may be referred to as an upper substrate, and the combination of the second base layer, the second electrode layer, the spacer, and the alignment layer may be referred to as a lower substrate. In a liquid crystal cell, the upper substrate does not include a separate alignment layer other than the adhesive layer, and the lower substrate may include an alignment layer.
[0084] The alignment film and the liquid crystal layer may be in contact with each other. The alignment film may be a vertical alignment film or a horizontal alignment film. In this specification, the term "horizontal alignment film" may refer to a layer containing an alignment material that imparts a horizontal alignment force to the liquid crystal compound present in the adjacent liquid crystal layer. In this specification, the term "vertical alignment film" may refer to a layer containing an alignment material that imparts a vertical alignment force to the liquid crystal compound present in the adjacent liquid crystal layer. The pretilt angle of the adjacent liquid crystal compound with respect to the vertical alignment film may be within a range of 80 degrees to 90 degrees, 85 degrees to 90 degrees, or about 87 degrees to 90 degrees, and the pretilt angle of the adjacent liquid crystal compound with respect to the horizontal alignment film may be within a range of 0 degrees to 10 degrees, 0 degrees to 5 degrees, or 0 degrees to 3 degrees. Unlike the adhesive layer, the alignment film may not have an adhesive force that bonds the upper substrate and the lower substrate. In one example, the alignment film may have a peel force close to 0 with respect to the upper substrate in the state of the liquid crystal cell of FIG. 1.
[0085] The alignment film may be a rubbing alignment film or a photo-alignment film. The alignment direction of the alignment film may be the rubbing direction in the case of a rubbing alignment film, and the direction of the irradiated polarized light in the case of a photo-alignment film. The alignment direction may be confirmed by a detection method using an absorbing linear polarizer. Specifically, the alignment direction may be confirmed by arranging an absorbing linear polarizer on one side of the liquid crystal layer in a state where the liquid crystal compound contained in the liquid crystal layer is horizontally aligned, and measuring the transmittance by rotating the polarizer 360 degrees. In the above state, when light is irradiated to the liquid crystal layer or the absorbing linear polarizer side and the brightness (transmittance) is measured on the other side, if the absorption axis or transmission axis coincides with the alignment direction of the liquid crystal alignment film, the transmittance tends to be low, but the alignment direction may be confirmed through a simulation that reflects the refractive index anisotropy of the applied liquid crystal compound. A method for confirming the alignment direction depending on the mode of the liquid crystal layer is well known, and the alignment direction of the alignment film may be confirmed by such a well-known method in the present application.
[0086] Examples of the alignment film include materials that are known to exhibit alignment ability through rubbing alignment, such as polyimide compounds, poly(vinyl alcohol) compounds, poly(amic acid) compounds, polystyrene compounds, polyamide compounds, and polyoxyethylene compounds, as well as polyimide compounds, polyamic acid compounds, polynorbornene compounds, phenylmaleimide copolymer compounds, polyvinylcinamate compounds, polyazobenzene compounds, polyethyleneimide compounds, polyvinylalcohol compounds, polyimide compounds, polyethylene compounds, polystyrene compounds, polyphenylenephthalamide compounds, polyester compounds, CMPI (chloromethylated The material may include, but is not limited to, one or more selected from the group consisting of materials known to be capable of exhibiting alignment ability upon light irradiation, such as a polyimide compound, a PVCI (polyvinylcinnamate) compound, and a polymethyl methacrylate compound.
[0087] The spacer 20c can maintain the distance between the upper and lower substrates. A liquid crystal layer can be present in the area where no spacer is present between the upper and lower substrates.
[0088] The spacer may be a patterned spacer. The spacer may have a column shape or a partition wall shape. In one example, the spacer may have a partition wall shape. When the spacer has a partition wall shape, it may be advantageous in terms of maintaining the height of the liquid crystal cell and improving the physical rigidity of the liquid crystal cell. The partition wall may divide the space between the lower substrate and the upper substrate into two or more spaces. In the area where the spacer is not present, other films or other layers present at the lower portion may be exposed. For example, the second electrode layer may be exposed in the area where the spacer is not present. The alignment film may cover the spacer and the second electrode layer exposed in the area where the spacer is not present. In a liquid crystal cell in which the upper substrate and the lower substrate are bonded, the alignment film present on the spacer of the lower substrate and the adhesive layer of the upper substrate may be in contact with each other.
[0089] The spacer-free region between the upper and lower substrates may contain liquid crystal compounds and the above-mentioned additives, such as dichroic dyes, chiral agents, etc. The shape of the spacer is not particularly limited, and may be applied without limitation to have multiple sides, such as a circle, an ellipse, or other polygonal shapes.
[0090] The spacer may include a curable resin. The type of the curable resin is not particularly limited, and may be, for example, a thermosetting resin or a photocurable resin, such as an ultraviolet curable resin. The thermosetting resin may be, for example, a silicone resin, a silicon resin, a furan resin, a polyurethane resin, an epoxy resin, an amino resin, a phenol resin, a urea resin, a polyester resin, or a melamine resin, but is not limited thereto. The ultraviolet curable resin may be, for example, an acrylic polymer, such as a polyester acrylate polymer, a polystyrene acrylate polymer, an epoxy acrylate polymer, a polyurethane acrylate polymer, or a polybutadiene acrylate polymer, a silicone acrylate polymer, or an alkyl acrylate polymer, but is not limited thereto.
[0091] The spacer may be formed by a patterning process. For example, the spacer may be formed by a photolithography process. The photolithography process may include a process of applying a curable resin composition onto a substrate layer or an electrode layer, and then irradiating ultraviolet light through a pattern mask. The pattern mask may be patterned into an ultraviolet light transmitting region and an ultraviolet light blocking region. The photolithography process may further include a process of washing the curable resin composition irradiated with ultraviolet light. The region irradiated with ultraviolet light is cured, and the region not irradiated with ultraviolet light remains in a liquid state, so that it can be patterned into a partition wall by removing it through a washing process. In the photolithography process, in order to easily separate the resin composition and the pattern mask after ultraviolet light irradiation, the pattern mask may be subjected to a release treatment or a release paper may be placed between the layer of the resin composition and the pattern mask.
[0092] The width (line width), interval (pitch), thickness, and area of the spacer may be appropriately selected within a range that does not impair the object of the present application. For example, the width (line width) of the spacer may be in the range of 10 μm to 500 μm or in the range of 10 μm to 50 μm. The interval (pitch) of the spacer may be in the range of 10 μm to 1000 μm or in the range of 100 μm to 1000 μm. The area of the spacer may be about 5% or more and 50% or less with respect to 100% of the total area of the second base layer. When the area of the spacer is within the above range, it may be advantageous to ensure excellent electro-optical properties while adequately ensuring the adhesion between the upper substrate and the lower substrate. The thickness of the spacer may be, for example, in the range of 1 μm to 30 μm or 3 μm to 20 μm.
[0093] The optical device may further include outer substrates bonded to both sides of the liquid crystal cell. The bonding between the liquid crystal cell and the outer substrates may be performed using an adhesive layer. In one example, as shown in FIG 2, the optical device may include a first outer substrate 101, a first adhesive layer 301, the liquid crystal cell 200, a second adhesive layer 302, and a second outer substrate 102 in this order.
[0094] The outer substrate can be bonded to the liquid crystal cell by a high-temperature and high-pressure autoclave process. During the autoclave process, pressure can be applied locally to the liquid crystal cell including the adhesive layer due to uneven melting of the adhesive layer, foreign matter, shrinkage and expansion of the base layer and the polarizer described below, etc., and such pressure on the liquid crystal cell may cause black spots due to compression after autoclaving. According to the present application, by controlling the storage modulus and tangent delta value at 110°C of the adhesive layer included in the liquid crystal cell, the adhesive layer is less deformed even when local pressure is applied, and the spacer is less likely to penetrate into the adhesive layer, so that black spots due to compression can be prevented.
[0095] The first outer substrate and the second outer substrate may be an inorganic substrate or a plastic substrate, independently. The inorganic substrate is not particularly limited, and a known inorganic substrate may be used. For example, the inorganic substrate may be a glass substrate having excellent light transmittance. The glass substrate may be, but is not limited to, a soda lime glass substrate, a general reinforced glass substrate, a borosilicate glass substrate, or an alkali-free glass substrate. The polymer substrate may be a cellulose film such as TAC (triacetyl cellulose) or DAC (diacetyl cellulose); a COP (cycloolefin copolymer) film such as a norbornene derivative; an acrylic film such as PAR (Polyacrylate) or PMMA (poly(methyl methacrylate); a PC (polycarbonate) film; a polyolefin film such as PE (polyethylene) or PP (polypropylene); a PVA (polyvinyl Examples of the materials that can be used include, but are not limited to, sulfone-based films such as polysulfone (PSF) films, polyphenylsulfone (PPS) films, and polyethersulfone (PES) films; polyetheretherketon (PEEK) films; polyetherimide (PEI) films; polyester-based films such as polyethylenenaphthalate (PEN) films and polyethyleneterephtalate (PET) films; and fluororesin films. The first and second outer substrates may each have a functional layer such as a coating layer of gold, silver, or a silicon compound such as silicon dioxide or silicon monoxide, or an anti-reflection layer, as required.
[0096] In one example, the first outer substrate and / or the second outer substrate may be a glass substrate.
[0097] The thickness of the first outer substrate and the second outer substrate may be about 0.3 mm or more. In other examples, the thickness may be about 0.5 mm or more, 1 mm or more, 1.5 mm or more, or about 2 mm or more, and may be about 10 mm or less, 9 mm or less, 8 mm or less, 7 mm or less, 6 mm or less, 5 mm or less, 4 mm or less, or about 3 mm or less.
[0098] The first outer substrate and the second outer substrate may be flat or curved. For example, the first outer substrate and the second outer substrate may be flat or curved, or one of them may be flat and the other curved. If both of them are curved, their curvatures or radii of curvature may be the same or different. In this specification, the curvature or radii of curvature may be measured by a method known in the art, for example, using a non-contact device such as a 2D Profile Laser Sensor, a Chromatic Confocal Line Sensor, or a 3D Measuring Confocal Microscopy. Methods for measuring the curvature or radii of curvature using such devices are well known.
[0099] The first and second outer substrates may have the same sign of curvature. In other words, the first and second outer substrates may be bent in the same direction. That is, in this case, the center of curvature of the first outer substrate and the center of curvature of the second outer substrate are located in the same portion among the upper and lower portions of the first and second outer substrates. When the first and second outer substrates are bent in the same direction, the first and second outer substrates can be bonded more efficiently with the adhesive layer, and the adhesive strength between the first and second outer substrates and the liquid crystal cell and / or polarizer after bonding can be more efficiently prevented from decreasing.
[0100] One side of the first adhesive layer may contact the first outer substrate. If no other components (e.g., a first polarizer described below) are further included between the first outer substrate and the liquid crystal cell, the other side of the first adhesive layer may contact the liquid crystal cell, and if other components are further included, the other side of the first adhesive layer may contact the other components. One side of the second adhesive layer may contact the second outer substrate. If no other components (e.g., a second polarizer described below) are further included between the second outer substrate and the liquid crystal cell, the other side of the second adhesive layer may contact the liquid crystal cell, and if other components are further included, the other side of the second adhesive layer may contact the other components.
[0101] The optical device may further include a first polarizer positioned between the first outer substrate and the liquid crystal cell, and a second polarizer positioned between the second outer substrate and the liquid crystal cell. Figure 2 exemplarily illustrates an optical device including a first polarizer 401 and a second polarizer 402. Specifically, the first polarizer may be positioned between the first adhesive layer and the liquid crystal cell, and the second polarizer may be positioned between the second adhesive layer and the liquid crystal cell.
[0102] When the optical device further includes a first polarizer and a second polarizer, the optical device may further include a third adhesive layer between the first polarizer and the liquid crystal cell, and a fourth adhesive layer between the second polarizer and the liquid crystal cell. FIG. 2 exemplarily illustrates an optical device including a third adhesive layer 303 and a fourth adhesive layer 304. One side of the third adhesive layer may contact the first polarizer, and the other side may contact the liquid crystal cell. One side of the fourth adhesive layer may contact the second polarizer, and the other side may contact the liquid crystal cell. In one example, when a protective film for a polarizer is formed on one side of the first polarizer facing the third adhesive layer, one side of the third adhesive layer may contact the protective film. In one example, when a protective film for a polarizer is formed on one side of the second polarizer facing the fourth adhesive layer, one side of the fourth adhesive layer may contact the protective film.
[0103] The term "polarizer" as used herein means a film, sheet, or element having a polarizing function. A polarizer is a functional element that can extract light vibrating in one direction from incident light vibrating in various directions.
[0104] The first polarizer and the second polarizer may each be an absorptive polarizer or a reflective polarizer. In this specification, an absorptive polarizer refers to an element that exhibits selective transmission and absorption properties for incident light. For example, a polarizer can transmit light that vibrates in one direction from incident light that vibrates in various directions, and absorb light that vibrates in the remaining directions. In this specification, a reflective polarizer refers to an element that exhibits selective transmission and reflection properties for incident light. For example, a polarizer can transmit light that vibrates in one direction from incident light that vibrates in various directions, and reflect light that vibrates in the remaining directions.
[0105] The absorptive polarizer may be, but is not limited to, a polarizing layer formed by dyeing a polymer stretched film such as a PVA (poly(vinyl alcohol)) stretched film with iodine, or a guest-host polarizing layer having a liquid crystal polymerized in an oriented state as a host and a dichroic dye aligned by the orientation of the liquid crystal as a guest.
[0106] The reflective polarizer may be, for example, a reflective polarizing layer known as a dual brightness enhancement film (DBEF) or a reflective polarizing layer formed by coating a liquid crystal compound such as lyotropic liquid crystal (LLC), but is not limited thereto.
[0107] The polarizer may be a linear polarizer. In this specification, a linear polarizer refers to a polarizer in which selectively transmitted light is linearly polarized light that vibrates in one direction, and selectively absorbed or reflected light is linearly polarized light that vibrates in a direction perpendicular to the vibration direction of the linearly polarized light. In the case of an absorptive linear polarizer, the light transmission axis and the light absorption axis may be perpendicular to each other. In the case of a reflective linear polarizer, the light transmission axis and the light reflection axis may be perpendicular to each other.
[0108] A protective film, an anti-reflection film, a retardation film, a surface treatment layer, etc. may be additionally formed on one or both sides of the first polarizer and the second polarizer. The retardation film may be, for example, a quarter wave plate or a half wave plate. The quarter wave plate may have an in-plane retardation value in the range of about 100 nm to 180 nm, 100 nm, or 150 nm for light with a wavelength of 550 nm. The half wave plate may have an in-plane retardation value in the range of about 200 nm to 300 nm, or 250 nm to 300 nm for light with a wavelength of 550 nm. The retardation film may be, for example, a polymer stretched film or a liquid crystal polymer film. A film made of a known material may be used as the protective film of the polarizing plate. As such a material, for example, a thermoplastic resin having excellent transparency, mechanical strength, thermal stability, moisture blocking property, or isotropy may be used. Examples of such resins include cellulose resins such as TAC (triacetyl cellulose), polyester resins, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth)acrylic resins, cyclic polyolefin resins such as norbornene resins, polyarylate resins, polystyrene resins, polyvinyl alcohol resins, and mixtures thereof. The first and second protective films may be films of the same material or films of different materials. Examples of adhesives used to attach the polarizer, retardation film, and protective film include, but are not limited to, acrylic adhesives, isocyanate adhesives, polyvinyl alcohol adhesives, gelatin adhesives, vinyl latex adhesives, and water-based polyesters.
[0109] The transmittance of the first polarizer and the second polarizer for light with a wavelength of 550 nm may be within a range of 40% to 50%, respectively. The transmittance may refer to the single transmittance of the polarizer for light with a wavelength of 550 nm. The single transmittance of the polarizer may be measured, for example, using a spectrometer (V7100, manufactured by Jasco). For example, the air may be set as the baseline while the polarizer sample (without the upper and lower protective films) is placed in the instrument, and the axis of the polarizer sample may be aligned vertically and horizontally with the axis of the reference polarizer to measure the transmittance of each, and then the single transmittance may be calculated.
[0110] The light transmission axis of the first polarizer and the light transmission axis of the second polarizer may be perpendicular to each other. Specifically, the angle between the light transmission axis of the first polarizer and the light transmission axis of the second polarizer may be within a range of 80 degrees to 100 degrees or 85 degrees to 95 degrees. When the light transmission axis of the first polarizer and the light transmission axis of the second polarizer are perpendicular to each other, light leakage may occur depending on the distance between the first polarizer and the second polarizer.
[0111] The thickness of each of the first to fourth adhesive layers may be 10 μm or more. The thickness of each of the first to fourth adhesive layers may be 50 μm or more, 100 μm or more, 150 μm or more, 200 μm or more, 250 μm or more, 300 μm or more, 350 μm or more, or 380 μm or more, and may be 2,000 μm or less, 1,800 μm or less, 1,600 μm or less, 1,400 μm or less, 1,200 μm or less, 1,000 μm or less, or 800 μm or less. When the thickness of each of the adhesive layers is within the above range, it may be advantageous to ensure structural stability and uniform appearance characteristics of the optical device by minimizing defects during the bonding process of the outer substrate.
[0112] In one example, the thickness of the first adhesive layer and the second adhesive layer may be 400 μm or more, 500 μm or more, 600 μm or more, or 700 μm or more, respectively, which may be advantageous in minimizing defects during the bonding process of the outer substrate, thereby ensuring structural stability and uniform appearance characteristics of the optical device.
[0113] In one example, the thickness of each of the third adhesive layer and the fourth adhesive layer may be 380 μm or less, which can minimize the distance between the first polarizer and the second polarizer to reduce light leakage and ensure the structural stability of the optical device.
[0114] The first to fourth adhesive layers may each have a single layer structure of one adhesive layer or a laminate of two or more sub-adhesive layers. The thickness and number of the sub-adhesive layers may be controlled in consideration of the desired thickness of the adhesive layer. In one example, the thickness of one adhesive layer or sub-adhesive layer of a single layer structure may be in the range of 100 μm to 500 μm or 300 μm to 400 μm.
[0115] As one example, the storage modulus of each of the first to fourth adhesive layers may be in the range of 1 MPa to 100 MPa. As another example, the storage modulus of each of the first to fourth adhesive layers may be 2 MPa or more or 4 MPa or more, and may be 100 MPa or less, 80 MPa or less, 60 MPa or less, 40 MPa or less, or 20 MPa or less. The storage modulus may be a value measured at a temperature of 25° C. and a frequency of 1 Hz.
[0116] As an example, the first to fourth adhesive layers may each have a Young's modulus (E) in the range of 0.1 MPa to 100 MPa. As another example, the Young's modulus (E) of the first to fourth adhesive layers may be 0.2 MPa or more, 0.4 MPa or more, 0.6 MPa or more, 0.8 MPa or more, 1 MPa or more, 5 MPa or more, or about 10 MPa or more, and about 95 MPa or less, 80 MPa or less, 75 MPa or less, 70 MPa or less, 65 MPa or less, 60 MPa or less, 55 MPa or less, or about 50 MPa or less. The Young's modulus (E) may be measured, for example, by a method specified in ASTM D882, and may be measured by cutting the film into a shape specified in the corresponding standard and using equipment capable of measuring a stress-strain curve (capable of simultaneously measuring force and length), for example, a universal testing machine (UTM). When the Young's modulus of the adhesive layer included in the optical device is within the above range, it may be more advantageous to ensure excellent durability of the optical device. When the adhesive layer is a laminate of at least two or more sub-adhesive layers, each of the sub-adhesive layers can satisfy the above-mentioned range of Young's modulus.
[0117] As one example, the first to fourth adhesive layers may each have a thermal expansion coefficient of 2,000 ppm / K or less. In other examples, the thermal expansion coefficient may be about 1,900 ppm / K or less, 1,700 ppm / K or less, 1,600 ppm / K or less, or about 1,500 ppm / K or less, or about 10 ppm / K or more, 20 ppm / K or more, 30 ppm / K or more, 40 ppm / K or more, 50 ppm / K or more, 60 ppm / K or more, 70 ppm / K or more, 80 ppm / K or more, 90 ppm / K or more, 100 ppm / K or more, 200 ppm / K or more, 300 ppm / K or more, 400 ppm / K or more, 500 ppm / K or more, 600 ppm / K or more, 700 ppm / K or more, or about 800 ppm / K or more. The thermal expansion coefficient of the adhesive layer can be measured, for example, according to the ASTM D696 standard, by cutting into a shape specified in the relevant standard and measuring the change in length per unit temperature to calculate the thermal expansion coefficient, or by a known method such as TMA (ThermoMechanic Analysis). If the thermal expansion coefficient of the adhesive layer included in the optical device is within the above range, it may be more advantageous to ensure excellent durability of the optical device. If the adhesive layer is a laminate of at least two or more sub-adhesive layers, each of the sub-adhesive layers may satisfy the above range of thermal expansion coefficient.
[0118] The first to fourth adhesive layers may be a thermoplastic polyurethane (TPU) adhesive layer, a polyamide adhesive layer, a polyester adhesive layer, an EVA (Ethylene Vinyl Acetate) adhesive layer, an acrylic adhesive layer, a silicone adhesive layer, or a polyolefin adhesive layer. According to one embodiment of the present application, the first to fourth adhesive layers may be a thermoplastic polyurethane adhesive layer.
[0119] The optical device may further include an outer layer surrounding a side of the liquid crystal cell. Figure 2 illustrates an example of an optical device including the outer layers 501 and 502. In the optical device, the area above the liquid crystal cell may be smaller than the area above the first outer substrate or the second outer substrate. Also, the area above the liquid crystal cell may be smaller than the area above the first to fourth adhesive layers included in the optical device.
[0120] In one example, the liquid crystal cell may be encapsulated by the adhesive layer and the outer layer. In the present application, the term encapsulation may mean covering the entire surface of the liquid crystal cell with the adhesive layer and the outer layer. In one example, when the optical device includes a first adhesive layer and a second adhesive layer, the liquid crystal cell may be encapsulated by the first adhesive layer, the second adhesive layer, and the outer layer. In one example, when the optical device includes a first adhesive layer, a second adhesive layer, a third adhesive layer, and a fourth adhesive layer, the liquid crystal cell may be encapsulated by the third adhesive layer, the fourth adhesive layer, and the outer layer. Such an encapsulation structure significantly improves the durability and weather resistance of the optical device, and as a result, the optical device may be stably applied to outdoor applications such as sunroofs.
[0121] The outer layer may include, for example, a thermoplastic polyurethane (TPU) adhesive, a polyamide adhesive, a polyester adhesive, an ethylene vinyl acetate (EVA) adhesive, an acrylic adhesive, a silicone adhesive, or a polyolefin adhesive. In one example, the outer layer may be formed of the same material as the adhesive layer.
[0122] The present application also relates to a method for manufacturing an optical device. The method for manufacturing the optical device may include a step of autoclaving a laminate including a first outer substrate, a first adhesive layer, a liquid crystal cell, a second adhesive layer, and a second outer substrate in that order. The liquid crystal cell may be encapsulated through the autoclaving. Unless otherwise specified, the same contents described in the optical device may be applied to the method for manufacturing the optical device.
[0123] The laminate may further include an outer layer surrounding a side surface of the liquid crystal cell.
[0124] When manufacturing an optical device further including a first polarizer and a second polarizer, the autoclave treatment can be performed on a laminate including, in order, a first outer substrate, a first adhesive layer, a first polarizer, a third adhesive layer, a liquid crystal cell, a second polarizer, a fourth adhesive layer, a second adhesive layer, and a second outer substrate.
[0125] When the optical device further includes other elements other than the liquid crystal cell and the polarizer, the laminate can further include the other elements other than the liquid crystal cell and the polarizer at desired positions.
[0126] The autoclaving step may be accomplished by applying heat and / or pressure to the laminate.
[0127] The conditions of the autoclave process are not particularly limited, and may be performed under appropriate temperature and pressure depending on the type of adhesive layer applied. The temperature of the typical autoclave process is about 80°C or more, 90°C or more, or 100°C or more, and the pressure is 2 atm or more, but is not limited thereto. The upper limit of the process temperature may be about 200°C or less, 190°C or less, 180°C or less, or 170°C or less, and the upper limit of the process pressure may be about 10 atm or less, 9 atm or less, 8 atm or less, 7 atm or less, or 6 atm or less.
[0128] The optical device may be a variable transmission device that can be switched between at least two states having different transmission levels. In one example, the variable transmission device may be a device that can be switched between a transmission and a blocking mode state.
[0129] The transmittance of the variable transmittance device in the transmission mode state may be at least 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, or 80%. In other examples, the transmittance in the transmission mode may be 100% or less, 95% or less, 90% or less, or 85% or less. However, since the higher the transmittance in the transmission mode, the more advantageous it is, the upper limit is not particularly limited.
[0130] The transmittance of the variable transmittance device in the blocking mode may be 60% or less, 55% or less, 50% or less, 45% or less, 40% or less, 35% or less, 30% or less, 25% or less, 20% or less, 15% or less, 10% or less, or 5% or less. In other examples, the transmittance in the blocking mode may be 0% or more, 5% or more, 10% or more, 15% or more, 20% or more, or 25% or more. However, since a lower transmittance is more advantageous in the blocking mode, the lower limit of the transmittance in the blocking mode is not particularly limited.
[0131] The transmittance may be, for example, a rectilinear light transmittance. The rectilinear light transmittance is a percentage of the ratio of light transmitted in the same direction as the incident direction to the light incident on the device. For example, if the device is in the form of a film or sheet, the transmittance can be defined as the percentage of light transmitted through the device in the direction aligned with the normal direction of the film or sheet surface, among the light incident in the direction aligned with the normal direction.
[0132] The transmittance may be the transmittance for any one wavelength in the visible light region, for example, within a range of about 400 to 700 nm or about 380 to 780 nm, the transmittance for the entire visible light region, the maximum or minimum transmittance among the transmittances for the entire visible light region, or the average value of the transmittances in the visible light region.
[0133] The optical device may be used in a variety of applications, such as eyewear, such as sunglasses, AR (Augmented Reality) or VR (Virtual Reality) eyewear, building exteriors, and vehicle sunroofs. In one example, the optical device may be a vehicle sunroof itself. For example, the optical device may be attached to at least one opening in a vehicle body having the vehicle body and used as a vehicle sunroof. Effect of the Invention
[0134] The present application relates to an optical device, in which the cell gap of a liquid crystal cell is properly maintained, the upper and lower substrates have excellent adhesion, and the optical device can be pressed after a high-temperature and high-pressure autoclave process to prevent black spots. [Brief description of the drawings]
[0135] [Figure 1] 1 illustrates an exemplary liquid crystal cell of the present application. [Diagram 2] 1 illustrates an exemplary optical device of the present application. [Diagram 3] 1 shows an image of Example 1 after autoclaving. [Figure 4] 1 shows an image of Example 2 after autoclaving. [Diagram 5] 1 shows an image of Example 3 after autoclaving. [Figure 6] 1 shows an image of Example 4 after autoclaving. [Figure 7] 1 shows an image of Example 5 after autoclaving. [Figure 8] 1 shows an image of Example 6 after autoclaving. [Figure 9] 1 shows an image of Comparative Example 1 after autoclaving. [Figure 10] 1 shows an image of Comparative Example 2 after autoclaving. [Figure 11] 1 shows an image of Comparative Example 3 after autoclaving. [Figure 12] 13 shows an enlarged image of a black spot in Comparative Example 1 and an example of the principle of black spot generation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0136] Hereinafter, the present application will be described in detail with reference to examples, but the scope of the present application is not limited to the following examples.
[0137] Example 1 Fabrication of the upper board An OCA type adhesive resin (KR3700, Shin-Etsu) was mixed with a toluene solvent to a solid content concentration of 25 wt%, and 15 parts by weight of crosslinker A (Tetrakis (Dimethylsiloxy) Silane, Gelest) and 1 part by weight of platinum catalyst (CAT-PL-56, Shin-Etsu) were added to 100 parts by weight of the adhesive resin to prepare an adhesive composition. The adhesive composition was coated on a fluorine release film (FSC6, Nippa) by bar coating, and then heated at 140°C for 6 minutes to form an adhesive layer A with a final thickness of about 10 μm. The adhesive layer was laminated on the ITO layer of a PET-ITO film to prepare an upper substrate. The PET-ITO film is a film in which an ITO (Indium Tin Oxide) layer is deposited to a thickness of about 30 nm on a highly oriented PET (polyethyleneterephthalate) film (OCF, SKC Corporation), with a total thickness of about 145 μm. The upper substrate has a structure in which a highly oriented PET film / ITO layer / adhesive layer / release film are laminated in this order.
[0138] Fabrication of the lower board An acrylic resin composition (product name: KAD-03, manufacturer: Minutatek) was coated on the ITO layer of the same PET-ITO film used for the upper substrate, and then photolithography was used to pattern it into a square shape to form a partition-like spacer. The partition height was 6μm, the pitch (the distance between two opposing sides of the square) was 350μm, and the line width was 15μm. Next, a vertical alignment film (5661LB3, Nissan) was coated on the spacer to a thickness of about 300nm, and then rubbed with a rubbing cloth to produce the lower substrate.
[0139] Liquid crystal cell bonding The fluorine release film was peeled off from the upper substrate. A liquid crystal composition was coated on the alignment layer of the lower substrate, and then the liquid crystal cell was bonded by laminating it with the upper substrate. The liquid crystal composition was a mixture of a liquid crystal compound (SHN-7002XX T12, JNC Co.) with a refractive index anisotropy (△) of 0.094 and negative dielectric anisotropy and a chiral additive (S811, Merck). The liquid crystal cell manufactured was a reverse TN mode liquid crystal cell with a cell gap of 6 μm and a chiral pitch of 20 μm.
[0140] Example 2 A liquid crystal cell was manufactured in the same manner as in Example 1, except that adhesive layer B was formed as follows instead of adhesive layer A in Example 1. An OCA type adhesive resin (KR3700, ShinEtsu Co., Ltd.) was mixed with a toluene solvent so that the solid concentration was 25 wt%, and 10 parts by weight of crosslinker B (n-Octadecyltrimethoxysilane, Gelest Co., Ltd.) and 1 part by weight of platinum catalyst (CAT-PL-56, ShinEtsu Co., Ltd.) were added to 100 parts by weight of the adhesive resin to prepare an adhesive composition. The adhesive composition was coated on a fluorine release film (FSC6, Nippa Co., Ltd.) by bar coating, and then heated at a temperature of 140° C. for 3 minutes to form an adhesive layer B with a final thickness of about 10 μm.
[0141] Example 3 A liquid crystal cell was manufactured in the same manner as in Example 1, except that adhesive layer C was formed as follows instead of adhesive layer A in Example 1. OCA type adhesive resin (KR3700, ShinEtsu Co., Ltd.) was mixed with a toluene solvent to a solid concentration of 25 wt%, and 3 parts by weight of crosslinker C (Dodecyltrimethoxysilane, Gelest Co., Ltd.) and 1 part by weight of platinum catalyst (CAT-PL-56, ShinEtsu Co., Ltd.) were added to 100 parts by weight of the adhesive resin to prepare an adhesive composition. The adhesive composition was coated on a fluorine release film (FSC6, Nippa Co., Ltd.) by bar coating, and then heated at a temperature of 140° C. for 3 minutes to form an adhesive layer C with a final thickness of about 10 μm.
[0142] Example 4 A liquid crystal cell was manufactured in the same manner as in Example 1, except that adhesive layer D was formed as follows instead of adhesive layer A in Example 1. An OCA type adhesive resin (KR3700, ShinEtsu Co., Ltd.) was mixed with a toluene solvent to a solid concentration of 25 wt%, and 15 parts by weight of crosslinker A (Tetrakis (Dimethylsiloxy) Silane, Gelest Co., Ltd.) and 1 part by weight of platinum catalyst (CAT-PL-56, ShinEtsu Co., Ltd.) were added to 100 parts by weight of the adhesive resin to prepare an adhesive composition. The adhesive composition was coated on a fluorine release film (FSC6, Nippa Co., Ltd.) by bar coating, and then heated at a temperature of 140°C for 3 minutes to form an adhesive layer D having a final thickness of about 10 μm.
[0143] Example 5 A liquid crystal cell was manufactured in the same manner as in Example 1, except that instead of the adhesive layer A in Example 1, an adhesive layer E was formed as follows. An OCA type adhesive resin (SS9242, KCC) was mixed with a toluene solvent so that the solid concentration was 25 wt%, and an adhesive composition was prepared by adding 1 part by weight of crosslinker D (S0016B, KCC), 3 parts by weight of crosslinker E (SC0025B, KCC), and 1 part by weight of platinum catalyst (SK0010C, KCC) to 100 parts by weight of the adhesive resin. The adhesive composition was coated on a fluorine release film (FSC6, Nippa) by bar coating, and then heated at a temperature of 140° C. for 6 minutes to form an adhesive layer E with a final thickness of about 10 μm.
[0144] Example 6 A liquid crystal cell was manufactured in the same manner as in Example 1, except that instead of the adhesive layer A in Example 1, an adhesive layer F was formed as follows. An OCA type adhesive resin (SS9242, KCC) was mixed with a toluene solvent so that the solid concentration was 25 wt%, and an adhesive composition was prepared by adding 0.5 parts by weight of crosslinker D (S0016B, KCC), 3.5 parts by weight of crosslinker E (SC0025B, KCC), and 1 part by weight of platinum catalyst (SK0010C, KCC) to 100 parts by weight of the adhesive resin. The adhesive composition was coated on a fluorine release film (FSC6, Nippa) by bar coating, and then heated at a temperature of 140° C. for 6 minutes to form an adhesive layer F with a final thickness of about 10 μm.
[0145] Comparative Example 1 A liquid crystal cell was manufactured in the same manner as in Example 1, except that instead of the adhesive layer A in Example 1, an adhesive layer G was formed as follows. An OCA type adhesive resin (KR3700, ShinEtsu Co., Ltd.) was mixed with a toluene solvent so that the solid concentration was 25 wt%, and 15 parts by weight of a crosslinking agent A (Tetrakis (Dimethylsiloxy) Silane, Gelest Co., Ltd.) and 1 part by weight of a platinum catalyst (CAT-PL-56, ShinEtsu Co., Ltd.) were added to 100 parts by weight of the adhesive resin to prepare an adhesive composition. The adhesive composition was coated on a fluorine release film (FSC6, Nippa Co., Ltd.) by bar coating, and then heated at a temperature of 140°C for 1 minute to form an adhesive layer G with a final thickness of about 10 μm.
[0146] Comparative Example 2 A liquid crystal cell was manufactured in the same manner as in Example 1, except that instead of the adhesive layer A in Example 1, an adhesive layer H was formed as follows. An OCA type adhesive resin (KR3700, ShinEtsu Co., Ltd.) was mixed with a toluene solvent to a solid concentration of 25 wt%, and 15 parts by weight of a crosslinking agent A (Tetrakis (Dimethylsiloxy) Silane, Gelest Co., Ltd.) and 1 part by weight of a platinum catalyst (CAT-PL-56, ShinEtsu Co., Ltd.) were added to 100 parts by weight of the adhesive resin to prepare an adhesive composition. The adhesive composition was coated on a fluorine release film (FSC6, Nippa Co., Ltd.) by bar coating, and then heated at a temperature of 130°C for 3 minutes to form an adhesive layer H having a final thickness of about 10 μm.
[0147] Comparative Example 3 A liquid crystal cell was manufactured in the same manner as in Example 1, except that adhesive layer I was formed as follows instead of adhesive layer A in Example 1. An OCA type adhesive resin (KR3700, ShinEtsu Co., Ltd.) was mixed with a toluene solvent to a solid concentration of 25 wt%, and 15 parts by weight of crosslinker A (Tetrakis (Dimethylsiloxy) Silane, Gelest Co., Ltd.) and 2 parts by weight of platinum catalyst (CAT-PL-56, ShinEtsu Co., Ltd.) were added to 100 parts by weight of the adhesive resin to prepare an adhesive composition. The adhesive composition was coated on a fluorine release film (FSC6, Nippa Co., Ltd.) by bar coating, and then heated at a temperature of 140°C for 3 minutes to form an adhesive layer I having a final thickness of about 10 μm.
[0148] Measurement example 1. Measurement of storage modulus and tangent delta value of adhesive layer The storage modulus and tangent delta value of the adhesive layer were measured using a TA ARES G2 Rheometer. As described in the Examples and Comparative Examples, an adhesive layer was formed on a fluorine release film, and the fluorine release film was then peeled off to remove the adhesive layer. A disk-shaped adhesive layer sample with a diameter of about 8 mm and a thickness of about 1000 μm was placed on an Al plate with a diameter of about 8 mm and the measurement was carried out. During the measurement, the storage modulus (G') and loss modulus (G") were measured, and the tangent delta value was calculated as G" / G'. The storage modulus and tangent delta values obtained under the conditions of a frequency of 1 rad / sec and a temperature of 110°C and those under the conditions of a frequency of 1 rad / sec and a temperature of 25°C are shown in Table 1 below.
[0149] Evaluation example 1. Evaluation of the occurrence of black spots after autoclaving A laminate was prepared which included, in order, a first outer substrate 101, a first adhesive layer 301, a first polarizer 401, a third adhesive layer 303, a liquid crystal cell 200, a fourth adhesive layer 304, a second polarizer 402, a second adhesive layer 302 and a second outer substrate 102, and which included outer layers 501, 502 surrounding the sides of the liquid crystal cell 200.
[0150] The liquid crystal cells used were the liquid crystal cells of Examples 1 to 6 and Comparative Examples 1 to 3. The first outer substrate was a glass substrate having a thickness of about 3 mm, an area of 1100 mm x 800 mm (horizontal x vertical), and a radius of curvature of about 2,470R. The second outer substrate was a glass substrate having a thickness of about 3 mm, an area of 1100 mm x 800 mm (horizontal x vertical), and a radius of curvature of about 2,400R. The first polarizer and the second polarizer were PVA polarizers, and the light transmission axis of the first polarizer and the light transmission axis of the second polarizer were arranged to form an angle of about 90 degrees. The first adhesive layer and the second adhesive layer were TPU layers (Argotec) having a thickness of 760 μm, and the third adhesive layer and the fourth adhesive layer were TPU layers (Argotec) having a thickness of 380 μm. The TPU layer (Argotec) had a thermal expansion coefficient of 307 ppm / K, a storage modulus of 3,357,730 Pa, and a loss modulus of 1,485,510 Pa.
[0151] The laminate was autoclaved at a temperature of about 110° C. and a pressure of about 3 atm for 3 hours to manufacture an optical device having the structure of FIG. 2. The optical device after the autoclaving was evaluated for the presence or absence of black spots, and the results are shown in Table 1 below. FIGS. 3 to 8 show images of Examples 1 to 6 after autoclaving, respectively. FIGS. 9 to 11 show images of Comparative Examples 1 to 3 after autoclaving, respectively. No black spots were observed after autoclaving in Examples 1 to 6, but black spots were observed after autoclaving in Comparative Examples 1 to 3. FIG. 12 shows an enlarged image of the black spots in Comparative Example 1 and an example of the principle of black spots (FIG. 12(A): before autoclaving, FIG. 12(B): after autoclaving, FIG. 12(C): enlarged black spots, FIG. 12(D): principle of black spots). FIG. 12(D) shows only the first base layer 10a, the adhesive layer 10c, the second base layer 20a, and the spacer 20c. In Figure 12 (B) and (C), the areas without black dots are areas where no pressure is being applied to the liquid crystal cell, and the areas with black dots are areas where pressure is being applied locally to the liquid crystal cell. When localized pressure is applied to a liquid crystal cell, the liquid crystals move due to the pressure (moving in the direction of the arrow in Figure 12 (D)) and the escaped areas appear as black dots, and when the moved liquid crystals gather together, liquid crystal clusters (bright areas around the black dots) occur.
[0152] [Table 1] [Explanation of symbols]
[0153] 10a: First base layer 10b: First electrode layer 10c:Adhesive layer 20a: Second base layer 20b: Second electrode layer 20c: Spacer 20d: Alignment film 30: Liquid crystal layer 101: First outer circuit board 102: Second outer circuit board 200: Liquid crystal cell 301: First adhesive layer 302: Second adhesive layer 303: 3rd adhesive layer 304: 4th adhesive layer 401: First polarizer 402: Second polarizer 501, 502: Outer layer
Claims
1. an upper substrate comprising a first base layer and an adhesive layer; a lower substrate including a second substrate layer and a spacer; and A liquid crystal layer including a liquid crystal compound between an upper substrate and a lower substrate, The pressure-sensitive adhesive layer has a storage modulus of 18,000 Pa or more at a temperature of 110° C. and a frequency of 1 rad / sec, and a tangent delta value of 0.32 or less at a temperature of 110° C. and a frequency of 1 rad / sec.
2. The optical device according to claim 1 , further comprising a first electrode layer between the first substrate layer and the pressure-sensitive adhesive layer, and further comprising a second electrode layer between the second substrate layer and the spacer.
3. The optical device of claim 1 , wherein the upper substrate does not include an alignment film, and the lower substrate further includes an alignment film.
4. The optical device of claim 1 , wherein the adhesive layer comprises a silicone adhesive.
5. 2. The optical device according to claim 1, wherein the pressure-sensitive adhesive layer has a storage modulus in the range of 18,000 Pa to 100,000 Pa at a temperature of 110° C. and a frequency of 1 rad / sec.
6. 2. The optical device according to claim 1, wherein the pressure-sensitive adhesive layer has a tangent delta value in the range of 0.1 to 0.32 at a temperature of 110° C. and a frequency of 1 rad / sec.
7. 2. The optical device according to claim 1, wherein the pressure-sensitive adhesive layer has a storage modulus of 10,000 Pa to 1,100,000 Pa at a temperature of 25° C. and a frequency of 1 rad / sec.
8. 2. The optical device according to claim 1, wherein the adhesive layer has a tangent delta value of 0.1 to 2.0 at a temperature of 25° C. and a frequency of 1 rad / sec.
9. The optical device of claim 1 , comprising, in order, a first outer substrate, a first adhesive layer, the liquid crystal cell, a second adhesive layer, and a second outer substrate.
10. The optical device of claim 9 , wherein the first outer substrate and the second outer substrate are each a glass substrate.
11. 10. The optical device of claim 9, wherein the first adhesive layer and the second adhesive layer are each a thermoplastic polyurethane (TPU) adhesive layer, a polyamide adhesive layer, a polyester adhesive layer, an EVA (Ethylene Vinyl Acetate) adhesive layer, an acrylic adhesive layer, a silicone adhesive layer, or a polyolefin adhesive layer.
12. 10. The optical device of claim 9, further comprising a first polarizer between the first adhesive layer and the liquid crystal cell and a second polarizer between the second adhesive layer and the liquid crystal cell.
13. The optical device of claim 12 , wherein a transmission axis of the first polarizer and a transmission axis of the second polarizer are orthogonal to each other.
14. 13. The optical device of claim 12, further comprising a third adhesive layer between the first polarizer and the liquid crystal cell and a fourth adhesive layer between the second polarizer and the liquid crystal cell.
15. 15. The optical device of claim 14, wherein the third adhesive layer and the fourth adhesive layer are each a thermoplastic polyurethane (TPU) adhesive layer, a polyamide adhesive layer, a polyester adhesive layer, an EVA (Ethylene Vinyl Acetate) adhesive layer, an acrylic adhesive layer, a silicone adhesive layer, or a polyolefin adhesive layer.
Citation Information
Patent Citations
Diffusion sheet and liquid crystal display device
JP2012226290A
Adhesive composition
JP2015536370A
Adhesive for optical film, adhesive layer for optical film, optical member and image display device
JP2016108555A
Adhesive composition for foldable displays
JP2019528330A
Photocurable adhesive sheet, photocurable adhesive sheet with release sheet, optical film with photocurable adhesive sheet, laminate for constituting image display device and image display device
JP2020125370A